2003
DOI: 10.1097/00001756-200312020-00020
|View full text |Cite
|
Sign up to set email alerts
|

Altered effective connectivity in drug free schizophrenic patients

Abstract: The present fMRI study aimed to investigate effective connectivity within a cortical-subcortical-cerebellar information processing network in drug free schizophrenic patients while performing a 2-back working memory task. The finding of enhanced thalamo-cortical and cortico-cortical intrahemispheric connectivity could be interpreted as a compensatory increase of neuronal connection strength consistent with a model of cortical inefficiency in schizophrenic patients. Additionally, the result could be integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 23 publications
7
18
0
1
Order By: Relevance
“…The measures derived with this method were highly reproducible in two repeated scans of a subset of the control subjects (ICC40.82); the effect size of the differences between diagnostic groups appeared robust (Cohen's dB0.8), and unlikely to be due to several possible confounding factors (eg, age and chlorpromazine equivalents). Our data offer a possible anatomical substrate for differences in functional connectivity between patients with schizophrenia and controls previously described with fMRI (Meda et al, 2010;Schlosser et al, 2003;Welsh et al, 2010;Zhou et al, 2007) and are consistent with a reduction in connectivity from multiple sources in the thalamus to the LPFC. Besides three studies showing that neurons specifically projecting to LPFC in the medio-dorsal nucleus of the thalamus may be reduced in schizophrenia (Byne et al, 2002;Popken et al, 2000;Young et al, 2000), reduced sizes of the pulvinar, of the centromedian nuclei (both projecting in part to the LPFC: Byne et al, 2007;Kemether et al, 2003) and reductions in oligodendrocyte number in the anterior principal nucleus (Byne et al, 2006(Byne et al, , 2008 were found in schizophrenia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The measures derived with this method were highly reproducible in two repeated scans of a subset of the control subjects (ICC40.82); the effect size of the differences between diagnostic groups appeared robust (Cohen's dB0.8), and unlikely to be due to several possible confounding factors (eg, age and chlorpromazine equivalents). Our data offer a possible anatomical substrate for differences in functional connectivity between patients with schizophrenia and controls previously described with fMRI (Meda et al, 2010;Schlosser et al, 2003;Welsh et al, 2010;Zhou et al, 2007) and are consistent with a reduction in connectivity from multiple sources in the thalamus to the LPFC. Besides three studies showing that neurons specifically projecting to LPFC in the medio-dorsal nucleus of the thalamus may be reduced in schizophrenia (Byne et al, 2002;Popken et al, 2000;Young et al, 2000), reduced sizes of the pulvinar, of the centromedian nuclei (both projecting in part to the LPFC: Byne et al, 2007;Kemether et al, 2003) and reductions in oligodendrocyte number in the anterior principal nucleus (Byne et al, 2006(Byne et al, , 2008 were found in schizophrenia.…”
Section: Discussionsupporting
confidence: 87%
“…Abnormalities in the medio-dorsal, pulvinar, and centromedian nuclei of the thalamus, all connected to the lateral prefrontal cortex (LPFC), a site of well-documented abnormalities in schizophrenia (Weinberger et al, 2001), have been reported with several methods (eg, Andrews et al, 2006;Byne et al, 2002;Byne et al, 2007;Harms et al, 2007;Hazlett et al, 1999;Kemether et al, 2003;Kessler et al, 2009;Kumari et al, 2010;Lehrer et al, 2005;Popken et al, 2000;Rose et al, 2006, but see, for example, Danos et al, 2005;Dorph-Petersen et al, 2004;Kreczmanski et al, 2007 for negative findings). Some functional MRI (fMRI) studies found abnormalities in the correlation between the activity in the thalamus and the PFC in schizophrenia (eg, Meda et al, 2010;Schlosser et al, 2003;Welsh et al, 2010;Zhou et al, 2007), which may reflect alterations in anatomical connectivity. Thus, the changes in the coordinated functioning of the PFC and the thalamus might be relevant to the pathophysiology of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The DLPFC, on the other hand, is responsible for higher order processing such as monitoring, comparison, and manipulation of information that is maintained in the IFG (Rowe et al, 2000;Wagner et al, 2001). Decreased FC between the IFG and DLPFC has been found in SCZ patients (Schlosser et al, 2003;Spence et al, 2000), which suggests a failure of functional integration between the IFG and DLPFC for SCZ patients. It needs to be mentioned that the risk allele carriers always showed negative FCs between the IFG and DLPFC during cognitive performance in this study, which may be because that the DLPFC was recruited when the IFG's activation was low (Egner, 2011;Petrides, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These methods provide a means of testing for interregional correlations in functional activity that show the largest changes across diagnostic groups or task conditions; strongly positive or negative correlations between regions imply that these regions are connected functionally [McKeown et al, 1998]. This approach has been applied with some success to studies of schizophrenia [Jacobsen et al, 2004;Jennings et al, 1998;Lawrie et al, 2002;Meyer-Lindenberg et al, 2001;Schlosser et al, 2003]. These studies provide increasing evidence that cognitive dysfunction in schizophrenia may involve not only impaired function of specific neuroanatomical regions, but also impairment in the ability to engage functional networks subserving specific cognitive challenges [e.g., Friston and Frith, 1995].…”
Section: Discussionmentioning
confidence: 99%